Application of Project Based Learning Model to Improve Student Learning Outcomes in Class VB Water Cycle Material SD Negeri 4 Banda Aceh City - Hamdan, Syahirah; Ulhaq, Nida Ihya (Jurnal Ilmiah Teunuleh, 2023)
Based on observations, one of the problems in SD Negeri 4 Kota Banda Aceh is the low learning outcomes of students in science subjects. The application of the Project Based Learning model can provide a pleasant atmosphere for students in learning water cycle material. This study used the type of Classroom Action Research (PTK). The subjects of this study amounted to 23 students of classes V-B SD Negeri 4 Banda Aceh City, data collection techniques were carried out by observation, documentation, and learning outcomes tests. The technique of analyzing data from observations of student activities is with percentage descriptive statistics and individual student learning outcomes data. Based on the results of research in cycles I, II, and III obtained the following data: (1) the results of observations on student activities in learning observed during three cycles, increased in each cycle, namely: student activity in cycle I reached 81.7% of the medium category, cycle II reached 86.1% of the good category, and cycle III reached 91.3% of the very good category. (2) the learning outcomes of students in the water cycle material have increased in cycle I of classical completeness criteria reaching 60.87% with an average value of 67, in cycle II classical completeness criteria of 78.26% with an average value of 82.6, while cycle III classical completeness criteria of 91.3% with an average value of 91. It was concluded that the Project Based Learning learning model on water cycle material can improve the learning outcomes of grade V students of SD Negeri 4 Banda Aceh City.